Modeling and simulation to extend fibre optic communication signal transmission using micro ring resonator - Nikoukar, Ali (2014)
Long-distance communication systems use high-bit-rate optical fibre, where dispersion and distortion of the signals cause technical difficulties and problems which have to be dealt with in order to optimize the efficiency and the reliability of such systems. Applying soliton transmission is an interesting method due mainly to its potential capability to overcome the effect of fibre dispersion and to provide all optical transmission systems. Optical solitons can be formed when a balance has been established between self-phase modulation and group velocity dispersion within the regime of anomalous dispersion. The consequent governing wave equation is of the nonlinear Schrodinger (NLS) type. In this thesis, a system of microring resonators (MRRs) connected to an optical modified add/drop filter is presented as a soliton pulse generator. The system uses chaotic signals generated by a Gaussian laser pulse and bright soliton propagating inside a nonlinear MRR system. The chaotic signals can be generated via a set of microring resonators, suitable for long distance communications. The obtained results show comparison of laser and generated solitonic signals over several distances. Then, the generation of solitonic signals using add/drop filter system connected to a series of micro ring resonators is demonstrated and the output of this model is compared to various disposition of the Bit Error Rate (BER) for soliton versus laser signals over 25, 50 and 100 Km distances. Thus, these types of signals can be used in optical indoor systems such as wireless personal area networks and transmission link using appropriate components such as transmitter, fibre optics, amplifier, and receiver.